Two forms of amyloidosis presentation in ENT - Silva, Maria Inês (2012)
Objective: To report two cases of amyloidosis with clinicalpresentation in Otolaryngology, as well as a theoretical reviewabout its pathology, including clinical presentation, diagnosisand therapeutic options.Methods: A retrospective study was made with two cases ofamyloidosis diagnosed in our department between 2003 and2010. We present a case of primary systemic amyloidosisassociated with Multiple Myeloma, with presentation inOtolaryngology, and a second case of localized amyloidosis inthe larynx.Results: Amyloidosis, either in its localized or systemic form, isrelatively rare in Otolaryngology. However, macroglossia is acommon symptom of systemic amyloidosis, occurring in up to20% of patients. The localized amyloidosis primarily affects thelarynx, thus being of great importance to the otolaryngologist.Conclusions: Amyloidosis should be part of the differentialdiagnosis in head and neck lesions, with mandatory exclusionof its systemic form.